On the Activity of Adelie Penguin (Pygoscelis Adeliae) at Cape Hinode, Prince Olav Coast, Antarctica (Reports of the Japanese Antarctic Research Expedition) - Masahiro AOYANAGI (National Institute of Polar Research, 1973)
1. The daytime activities of Adelie penguin adults of the small colony in the early guard stage were observed at Hinode Misaki (Cape Hinode, 68°09'S, 42°43'E) during the austral summer. 2. Notes were made on the following thirteen activities : going out of the colony entering into the colony loud mutual display quiet mutual display ecstatic display bill-to-axilla display copulation turning egg over preening collecting nest stones fighting feeding and protective threatening against skuas. 3. The midday maximum activities were as follows : going out of the colony entering into the colony collecting nest stones loud mutual display copulation. The midday minimum activities were as follows : ecstatic display bill-to-axilla display. Frequency of activity was reverse between loud mutual display and quiet mutual display. Protective threatening varied with the activity of skua. In the activities of fighting, preening, feeding and turning egg over, no characteristic patterns were observed.